The Physiological Functions of the Golgin Vesicle Tethering Proteins - Lowe, Martin (Frontiers in Cell and Developmental Biology, 2019)
The golgins comprise a family of vesicle tethering proteins that act in a selective manner to tether transport vesicles at the Golgi apparatus. Tethering is followed by membrane fusion to complete the delivery of vesicle-bound cargo to the Golgi. Different golgins are localized to different regions of the Golgi, and their ability to selectively tether transport vesicles is important for the specificity of vesicle traffic in the secretory pathway. In recent years, our mechanistic understanding of golgin-mediated tethering has greatly improved. We are also beginning to appreciate how the loss of golgin function can impact upon physiological processes through the use of animal models and the study of human disease. These approaches have revealed that loss of a golgin causes tissue-restricted phenotypes, which can vary in severity and the cell types affected. In many cases, it is possible to attribute these phenotypes to a defect in vesicular traffic, although why certain tissues are sensitive to loss of a particular golgin is still, in most cases, unclear. Here, I will summarize recent progress in our understanding of golgins, focusing on the physiological roles of these proteins, as determined from animal models and the study of disease in humans. I will describe what these in vivo analyses have taught us, as well as highlight less understood aspects, and areas for future investigations.